Democracy: the war and the word". Political Elements of Communication in the Classical Greek pólis - Escanilla Segovia, Camila (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
This article examines the importance of the word in the development of politics in classical Greece, the precision of words and oral expression. At the same time the role and relevance of war, especially stasis, in the evolution of democracy and life in the Greek pólis.